Physicochemical and Functional Potential of Hydrocolloids Extracted from Some Solanaceae Plants - Kiran Aftab; Shabana Hameed; Huma Umbreen; Shafaqat Ali; Muhammad Rizwan; Saad Alkahtani; Mohamed M. Abdel-Daim (Journal of Chemistry)
Three different plants (Solanum indicum, Solanum surattense, and Solanum nigrum) of Solanaceae family were explored to extract and characterize hydrocolloids in aqueous solution. S. indicum fruit fractions bring in maximum hydrocolloid yield of 21.39 ± 0.42% based on % dry weight of the sample. The observed order of extracting hydrocolloid yield amongst investigating aerial parts of S. surattense, S. nigrum, and S. indicum (% dry weight) is fruits > stem > leaves. Maximum protein (22%) and starch (0.85%) contents were observed in fruit fractions of S. nigrum and S. indicum, respectively. Among the functional characteristics, the fruit fraction of S. indicum has higher water-holding capacity (24.80%), oil-holding capacity (2.96%), emulsifying activity (90%), emulsion stability (70%), foaming capacity (65%), and foaming stability (90%). Monosaccharide profiling results showed the presence of glucose, galacturonic acid, galactose, glucuronic acid, arabinose, and xylose in extracted fractions. The findings propose that hydrocolloids (extracted with water) are cost-effective and would be potential candidate as a substitute for pectin added into foamy and frothy food products and frothy beverages.